The Role of ChatGPT in Improving Cross-Cultural Team Management Performance - Elsya Meida Arif; Sarwo Sarwo; Ahmad Soderi; Abdur Rohman; Tribowo Rachmat Fauzan (Politeknik Ganesha Medan, 2023)
In this era of advanced globalisation, intercultural collaboration has become commonplace in business and organisational environments. Companies and organisations often form cross-cultural teams consisting of individuals from different cultural backgrounds, languages and values. These cross-cultural teams have great potential to provide a competitive advantage due to the combination of diverse knowledge and perspectives, but can also face challenges in effective team management and performance. This research aims to explore and explore the potential of ChatGPT utilisation in improving cross-cultural team management performance. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that the use of ChatGPT in cross-cultural team management brings great benefits to companies and organisations operating in a global business environment. As a form of next-generation Artificial Intelligence, ChatGPT can facilitate cross-cultural communication, increase understanding of cultural differences, and help better manage conflict. Features such as language translation, sentiment analysis, and intercultural skills training contribute to more efficient and creative team performance.